Nouvelles temporalités, changements spatiaux et inégalités sociales. L’exemple des villes pétrolières du Casanare (Colombie) - Jean-Marc Fournier (Cybergeo)
Taking the example of oil producing cities of Colombia, some links between reconstruction of times and modification of geographical spaces are established. From a social geography viewpoint, the consequences of these changes related with social inequalities are investigated. It is possible to identify time spaces, some of them only sketches, others very strongly defined: oil time spaces linked to globalization, time spaces of the “travelling” upper classes, time spaces of the oil-workers, time spaces of the more popular social classes living in the suburbs, the very fluctuating time spaces of guerrilla warfare, festive time spaces now become more commercial, time spaces of speculators thwarting urban planning, etc.